Halal Tourism: A Systematic Literature Review - Azidni Rofiqo Zidni; Mahfud Sholihin; Syafiq Mahmadah Hanafi; Asadillah Irsyad Maulana (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2022)
Purpose: This study aims to analyze the article has been the most influential; underlying references that influenced; and the main subjects and issues related to halal tourism. Methodology: The Systematic Literature Review (SLR) method is used in collecting and analyzing a set of articles that are considered to be related to the topic of the study. While for data analysis, bibliometry, Scopus analyzer and VOSviewer are used. The keywords 'Halal Tourism' and 'Islamic Tourism' using this study. A total of 64 selected articles were obtained during the search and filtering process. Findings: The findings of the study reviewed from the development of research trends show that research on the halal tourism or Islamic tourism between 2001 and 2020 tends to be volatile. There is 1 type of journal from a total of 35 journals, namely Journal of Islamic Marketing that produces the highest number of articles among other journals. Hamira Zamani-Farhani's research became more widely cited research in halal tourism research. Mohamed Buttor is a prdouctive writer who influences halal tourism research. The main topics and trends in the discussion of halal tourism are divided into tird topics. Firstly, 45% of them are related to tourism concept. Secondly, 16% discuss tourism industry. Third, 55% concern tourism management.